Carbohydrate-electrolyte feedings and 1h time trial cycling performance - Desbrow, B.; Anderson, S.; Barrett, J.; Rao, E.; Hargreaves, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
The effects of a commercial sports drink on performance in high-intensity cycling was investigated. Nine well-trained subjects were asked to complete a set amount of work as fast as possible (time trial) following 24 h of dietary (subjects were provided with food, energy 57.4 ± 2.4 kcal/kg and carbohydrate 9.1 ± 0.4 g/kg) and exercise control. During exercise, subjects were provided with 14mL/kg of either 6% carbohydrate-electrolyte (CHO-E) solution or carbohydrate-free placebo (P). Results showed that subjects` performances did not greatly improve (time, 62:34 ± 6:44 min:sec (CHO-E) vs. 62:40 ± 5:35 min:sec (P); average power output, 283.0 ± 25.0W (CHO-E) vs. 282.9 ± 29.3 (P), P > 0.05) while consuming the sports drink. It was concluded that CHO-E consumption throughout a 1-h time trial, following a pre-exercise dietary regimen designed to optimize glucose availability, did not improve time or power output to a greater degree than P in well-trained cyclists.